Nature-Based Recreation, Spirituality and Persons with Disabilities - Heintzman, Paul (Journal of disability & religion, 2014)
This article synthesizes empirical studies that explain the relationship between nature-based recreation and spirituality for persons with disabilities. In order to describe this relationship, a theoretical model, which includes the components of antecedent conditions, setting, and recreation, is developed. Antecedent conditions include history and current circumstances, motivation, sociodemographic characteristics, and spiritual tradition. Setting components include being in nature, being away to a different environment, and place processes. Recreation components include activity, free time, solitude, and group experiences. The article further explains how these conditions and components may lead to outcomes of spiritual experiences, spiritual well-being, and leisure-spiritual coping. Leisure-spiritual coping, which is particularly relevant for persons who are experiencing stress, refers to spiritual coping that takes place within the context of a person's leisure. This model illustrates the complexity of the nature-based recreation and spirituality relationship. Recommendations for future research and implications for practitioners who work with people who have disabilities are outlined.